2017
DOI: 10.1111/myc.12633
|View full text |Cite
|
Sign up to set email alerts
|

Performance of mycology and histopathology tests for the diagnosis of toenail onychomycosis due to filamentous fungi: Dermatophyte and non‐dermatophyte moulds

Abstract: Improvement of laboratory diagnosis of onychomychosis is important so that adequate treatment can be safely implemented. To evaluate and compare the performance of mycological and histopathological examinations in onychomycoses caused by dermatophyte and non-dermatophyte moulds. Patients with lateral/distal subungual onychomycosis in at least one hallux were enrolled in the protocol and assessed via mycological and histopathological tests. The isolation of filamentous fungi was considered the gold standard. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
16
2
Order By: Relevance
“…17 Of note, this study was one of the few studies reviewed that found KOH and direct microscopy to be more sensitive than PAS and/or GMS, detecting an additional 40 positive cases, including non-dermatophyte pathogenic molds. 17 In contrast, Karaman et al found that GMS detected more than twice the number of onychomycosis cases than PAS (70 by GMS and 32 by PAS). By a latent class analysis, GMS was determined to have both high sensitivity and specificity, and it was recommended that GMS be used as a confirmatory test after screening with KOH and direct microscopy.…”
Section: Pas or Gms As An Ancillary Test To Diagnose Onychomycosismentioning
confidence: 81%
See 2 more Smart Citations
“…17 Of note, this study was one of the few studies reviewed that found KOH and direct microscopy to be more sensitive than PAS and/or GMS, detecting an additional 40 positive cases, including non-dermatophyte pathogenic molds. 17 In contrast, Karaman et al found that GMS detected more than twice the number of onychomycosis cases than PAS (70 by GMS and 32 by PAS). By a latent class analysis, GMS was determined to have both high sensitivity and specificity, and it was recommended that GMS be used as a confirmatory test after screening with KOH and direct microscopy.…”
Section: Pas or Gms As An Ancillary Test To Diagnose Onychomycosismentioning
confidence: 81%
“…Due at least in part to the differences in study design, the prevalence of PAS and/or GMS positivity showed considerable variability. Supporting Information Table S1 [5][6][7][8][9][10][11][12][13][14][15][16][17] outlines all of the studies regarding onychomycosis detection methods and their findings.…”
Section: Pas or Gms As An Ancillary Test To Diagnose Onychomycosismentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published meta‐analysis has evaluated the utility of direct microscopic examination, culture, and histological examination for the diagnosis of onychomycosis . In the included studies of this meta‐analysis and similar studies, the positivity rates of these diagnostic methods have shown wide ranges (Table ). This rate was ranged from 23 to 77% for KOH, from 10 to 68% for culture, and from 38 to 80% for PAS.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the most recent years, comparative studies have still been done to evaluate the value of these methods in the diagnosis of onychomycosis . However, there is no real gold standard to calculate their sensitivities and specificities.…”
Section: Introductionmentioning
confidence: 99%